Detection of Atypical Motile Staphylococcus aureus from Rain Floods - Agha, Yusra; Najim, Ashwak Hazem; Talaat, Reem Ayad; Bahjat, Shababa Abdulatife (Open Access Macedonian Journal of Medical Sciences, 2022)
Abstract: Heavy rain floods is one of the primary risk factors for human health, and it can significantly regulate microbial communities and enhance the transfer of infections within the affected areas. Recently, the flood crisis is becoming one of the severe natural events in Mosul / Iraq. It may continue for months during which samples of accumulated rainwater were collected. Twelve Staphylococcus aureus were isolated by using two selective media: Mannitol Salt agar and Vogel-Johnson media in addition to Blood agar. An unusual colony spreading which resembles. "Bacillus colonies in twelve Staphylococcus aureus isolates was observed on Mannitol Salt agar and semisolid nutrient agar. Actively motile cocci in single and cluster arrangements that is not characteristic of brownian movement was shown in wet mount microscopic observation Furthermore, biosurfactant detection by oil spreading method ( oil displacement activity) showed that all isolates demonstrated various degrees of surfactant production which has beeen reported. to be responsible for stimulating "colony spreading" phenomenon in S. aureux. Motility can play a crucial role for survival bacterial species by which they get nutrients, avoid toxins and predators, and genetic information exchange by mating. The present study highlights for the first time. Mosul city a motile opportunistic aureus obtained from harvested rainwater samples during high-rainfall periods. Utilization of untreated harvested rainwater could thus offer a significant health threat to consumers, especially children. and immunocompromised individuals.